On the Solvability of Impulsive Differential-Algebraic Equations - Vlasenko, L. A.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish theorems on the existence and uniqueness of a solution of the impulsive differential-algebraic equation ddt [Au(t)] + Bu(t) = f(t,u(t)), where the matrix A may be singular. The results are applied to the theory of electric circuits.